The Predictive Power of Machine Learning Compared to Traditional Models in Stock Market Forecasting - Huutoniemi, Lauri (My University, 2026)
The purpose of this thesis is to investigate how machine learning can help stock market and how different models perform compared with traditional financial methods. The study also examines how data quality, feature selection, and market conditions influence forecasting accuracy. The motivation for this research arises from the limitations of traditional financial models. These models often assume stable relationships even though financial markets are complex and constantly changing. The thesis reviews theoretical background related to market efficiency and behavioral finance, which help explain why predicting stock prices is difficult. Behavioral finance shows that investors do not always act rationally, and for example psychological factors can affect price movements. Because of this, traditional econometric models do not always fully describe real market behaviour. Previous research shows that machine learning models can produce more accurate forecasts than traditional forecasting methods. For example, Random Forest, Support Vector Machines and deep learning models have shown promising results. However, result may vary depending on data quality and market situations. Also, practical forecasting use for the models have been discussed. With strengths and limitations, machine learning is showing to work better as a supportive tool rather than a complete replacement for traditional financial analysis.

Tämän tutkielman tavoitteena on selvittää, miten koneoppimista voidaan hyödyntää osakemarkkinoiden ennustamisessa ja miten eri mallit toimivat verrattuna perinteisiin taloudellisiin ennustemenetelmiin. Lisäksi työssä tarkastellaan, miten datan laatu, muuttujien valinta sekä markkinaolosuhteet vaikuttavat ennusteiden tarkkuuteen. Tutkimuksen lähtökohtana ovat perinteisten rahoitusmallien rajoitteet, sillä ne olettavat usein markkinoiden käyttäytyvän vakaasti, vaikka todellisuudessa markkinat ovat monimutkaisia ja jatkuvasti muuttuvia. Työssä käydään läpi markkinoiden tehokkuuteen ja käyttäytymistaloustieteeseen liittyvää teoriaa, jotka auttavat ymmärtämään, miksi osakekurssien ennustaminen on vaikeaa. Käyttäytymistaloustiede osoittaa, etteivät sijoittajat aina toimi täysin rationaalisesti, ja esimerkiksi psykologiset tekijät voivat vaikuttaa hintojen liikkeisiin. Tämän vuoksi perinteiset ekonometriset mallit eivät aina kuvaa markkinoiden todellista käyttäytymistä kovin hyvin. Aiempi tutkimus osoittaa, että koneoppimismallit voivat monissa tapauksissa tuottaa tarkempia ennusteita kuin perinteiset menetelmät. Esimerkiksi Random Forest-, Support Vector Machine- ja syväoppimismallit ovat antaneet lupaavia tuloksia. Tulokset kuitenkin vaihtelevat riippuen käytetystä datasta ja markkinatilanteesta. Tutkimuksissa on myös korostettu mallien käytännön soveltamisen haasteita. Sekä vahvuuksista että rajoitteista huolimatta koneoppiminen näyttää toimivan paremmin ennustamisen tukena kuin täysin perinteisten analyysimenetelmien korvaajana.
Keywords: machine learning; stock prices; economic forecasts; artificial intelligence; investment activities; data acquisition; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Rahoitus